Morphological descriptor for DUS testing of Indian jujube (Ziziphus mauritiana) - KRISHNA, HARE; BHARGAVA, R; CHAUHAN, NITESH; SHARMA, S K (The Indian Journal of Agricultural Sciences, 2016)
A total of 24 varieties of Indian jujube or ber (Ziziphus mauritiana Lamk.) were characterized based on morphological characters, viz. growth habit, foliage, thorn, fruit and stone. The erect growth habit was noticed in two varieties, viz. Dharki No. 1 and Tikadi, while semi-erect growth habit was noticed in majority of the varieties. Three types of leaf shapes were recorded, i.e. ovate, oval and cordate. Dharki No.1 and Safeda Rohtak had ovate leaf shape and Chhuhara Bawal, Jogia, Kaithali, Kala Gola, Katha Phal, Mehrun, Sanaur-5, Seb and Tikadi had cordate shape. While rest of the varieties showed oval shape. Ber varieties could also be categorized based on leaf pubescence on lower side, viz. smooth, sparsely-tomentose and densely-tomentose. Of which, only Tikadi exhibited smooth surface on lower leaf side. Also, Tikadi recorded high branch thorniness. On the basis of fruit maturity, varieties were grouped into early, mid and late. High variability was recorded for the character fruit shape (oblong, oval, ovate, oblate, round and falcate). Eleven varieties showed yellow, 12 varieties depicted greenish-yellow and one variety Tikadi, showed chocolate brown fruit colour at maturity. The varieties were also classified into five groups, on the basis of stone shape, viz. oblong, oval, spindle, club and falcate. The varieties depicted wide variability for various morphological traits, perhaps owing to such differences in the species from which these cultivars have evolved.